Topological proton regulation of interlayered local structure in sodium titanite for wide‐temperature sodium storage - Ru‐Ning Tian; Siwei Zhao; Zhuoran Lv; Guozhong Lu; Mengnuo Fu; Jingjing Chen; Dajian Wang; Chenlong Dong; Zhiyong Mao (Carbon Energy, 2024)
Abstract Developing high‐capacity and high‐rate anodes is significant to engineering sodium‐ion batteries with high energy density and high power density. Layered Na2Ti3O7 (NTO), with an open crystal structure, large theoretical capacity, and low working potential, is recognized as one of the prospective anodes for sodium storage. Nevertheless, it suffers from sluggish sodiation kinetics and low (micro)structure stability triggered by a high Na+ diffusion barrier and weak adhesion of [Ti3O7] slabs. Herein, the interlayered local structure of NTO is regulated to solve the above issues, in which parts of interlayered Na+ sites are substituted by H+ (Na2−xHxTi3O7 [NHTO]). Theoretical calculations prove that the NHTO offers lower activation energy for Na+ transports and low interlayer spacings with alleviated Na–Na repulsion and relatively flexible [Ti3O7] slabs to reduce fractural stress. In situ and ex situ characterizations of (micro)structure evolution reveal that NHTO goes through transformation between H‐rich and Na‐rich phases, resulting in high structure stability and microstructure integrity. The optimal NHTO anode delivers a high capacity of 190.6 mA h g−1 at 0.5 C after 300 cycles and a superior high‐rate stability of 90.6 mA h g−1 at 50 C over 10,000 cycles at room temperature. Besides, it offers a capacity of 50.3 mA h g−1 after 1800 cycles at a low temperature of −20°C and 195.7 mA h g−1 after 500 cycles at a high temperature of 40°C at 0.5 C. The developed topologically interlayered local structure regulation strategy would raise the prospect of designing high‐performance layered anodes.